KUALITAS PELAYANAN DALAM JASA TRANSPORTASI PUBLIK BUS RAPID TRANSIT (BRT) KOTA SEMARANG - Prayoga, Thoriq Adi; Subowo, Ari; Lituhayu, Dyah (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2015)
The high use of private vehicles and public transportation causing congestion on most roads in the city of Semarang . To reduce the congestion Semarang city government provide an alternative solution , namely policy Trans Bus Rapid ( BRT ) . However , in practice there are few facilities of BRT are not running optimally .